A Study on Speaking Skill of Traffic Police in Pekanbaru - Syaifullah Syaifullah; Marisa Marisa; Herlinawati Herlinawati (ELT-Lectura, 2023)
Abstract This study investigated the occupational English language needs of traffic police officers in Pekanbaru. Most police officers are graduates of the Police Academy. To study at the Police Academy, students must first complete either a high school or one of the four Police Academies. Although the intensive language training in the Police Academy is often considered adequate for most officers' needs, those officers who come from other backgrounds are often left behind. Even in the case of the Police Academy graduates, all their English language training is based on the principles of General English, and does not necessarily prepare them for the occupational-specific language needs they face on the job. This study set out to explore therefore, exactly to what extent the traffic police officers' English language knowledge is in fact adequate. Data, in this study, were collected by observing, making a conversation, recording, and taking notes. In collecting the data, the writer takes an involvement with the subject’s conversation every week whether as an active participant or only as an observer. The tool that can be used in collecting the data is a pen, a book, and a hand phone, this tools use for documenting the interaction between traffic police with foreigners. The observation can be done when the subjects making a conversation with the foreigners. As a result, most of them are reluctant to communicate with foreigners event with their partner. Keywords: A Study, Speaking Skill, Traffic Police